The distribution and movement patterns of four woodland caribou herds in Quebec and Labrador - Brown, W. K.; Huot, J.; Lamothe, P.; Luttich, S.; Paré, M.; Martin, G. St.; Theberge, J. B. (Rangifer, 1986)
Recent studies of woodland caribou (Rangifer tarandus caribou) in northern Quebec and central Labrador have demonstrated similar patterns of seasonal movements and distribution among four herds. Aerial surveys and radio-telemetry indicated that animals occupied forest-wetland habitat at densities of 0.03 caribou km2, or lower, for most of the year. Although females were widely dispersed at calving individuals demonstrated fidelity toward specific calving locations, in successive years. Caribou did not form large post-calving aggregations. Movement was greatest in the spring, prior to calving, and in the fall, during or immediately after rutting. Caribou were generally sedentary during summer and winter, although some moved relatively long distances to late-winter range. Although the herds occupy continuous range across Quebec and Labrador, our data indicate that the herds are largely discreete and should be managed individually.